PEMBUATAN E-MODUL BERBASIS INKUIRI TERSTRUKTUR PADA MATERI GERAK DAN GAYA UNTUK PEMBELAJARAN IPA KELAS VIII SMP/MTs - Egi Putrima Mulya; Amali Putra; Nurhayati Nurhayati (PILLAR OF PHYSICS EDUCATION, 2017)
The background of this research is a learning process that not optimize yet learners to form his own knowledge and this is because the learning process is still centered on the teacher, the limited teaching materials in e-modules form use of ICT as a medium of teaching or learning resources are not maximal. An alternative solution of this problem is the e-modules teaching materials in the form of structured inquiry-based modules. This study aims to produce teaching materials in the form of e-module structured inquiry based on the motion and force that proper use is used for learning science. This study is a Research and Development (R & D) that uses three stages of 4-D models, define, design, and develop, whereas disseminate is not done. Data collection instruments that is used in this study was a questionnaire validation and practicalities.In developmen t stage was validated by the 6 validators, and the practicalities stage was done by two teachers and 32 students of class VIII SMPN 11 Padang. The data of the research is primary data that consists of validity data and practicalities. The datas were analyzed with the descriptive analysis in the form of a percentage. The results showed that, the feasibility of e-module structured inquiry based on motion and force for science learning in class VIII of SMP / MTs can be seen from the results of the validation test that is average value 86.4072% with very valid and the result of practicalities of teachers with the average value of 81.6667% with practical criteria, while the results of the practicalities of learners average value 84.974% with practical criteria. It can be concluded that the e-module structured inquiry based on motion and force matter for science learning in class VIII SMP / MTs are made which have very valid and practical criteria